Differences in TRAIL-induced changes of Mcl-1 expression among distinct human colon epithelial cell lines - Hyršlová Vaculová, Alena; Hofmanová, Jiřina; Procházková, Jiřina; Kozubík, Alois (Experimental cell research, 2009)
In addition to its ability to act as a promising inducer of tumor-specific cell death, TRAIL has also been shown to stimulate signaling pathways leading to cancer cell survival. We examined the changes of anti-apoptotic Mcl-1 protein level following TRAIL treatment of human cell lines representing different stages of colon carcinogenesis-adenocarcinoma (HT-29, HCT116) or secondary metastasis (SW620), together with cell line derived from human fetal colon (FHC). While TRAIL was capable of triggering an anti-apoptotic signaling leading to significant early ERK-mediated transcriptional up-regulation of Mcl-1 in selected colon adenocarcinoma cell lines, none or very limited effects were demonstrated in cell lines derived from colon lymph node metastasis or fetal colon, respectively. We demonstrated an immediate impact of Mcl-1 protein level manipulations on the course of early acute apoptotic response of colon adenocarcinoma cells to TRAIL. It is therefore essential to consider the dynamics of modulation of Mcl-1 level and the balance between TRAIL-induced pro- and anti-apoptotic pathways when predicting the response of cells in different stages of cancer development, and designing the anticancer therapy using TRAIL.
Keywords: metastázy nádorů; Colonic Neoplasms; nádory tračníku; regulace genové exprese; lidé; Cell Survival; Gene Expression Regulation; Proto-Oncogene Proteins c-bcl-2; viabilita buněk; Epithelial Cells; protoonkogenní proteiny c-bcl-2; Neoplasm Metastasis; Cell Line, Tumor; TNF-Related Apoptosis-Inducing Ligand; epitelové buňky; nádorové buněčné linie; protein TRAIL; Humans